Corporate Acquisitions and Labor Rights: Who Protects the Workers? - Padot Agustinus Naibaho; Eman Suparman; Muhammad Amirulloh (Universitas Negeri Semarang, 2024)
The rapid evolution of the labor market, accelerated by the ASEAN Economic Community and an influx of job seekers, intensifies competition not only for employment but also for career stability within companies. At the same time, businesses face mounting pressure to stay competitive, often turning to mergers and acquisitions as a strategy for growth and survival. Yet, while these corporate moves may strengthen business prospects, they often leave workers in a precarious position, facing potential job loss or uncertain changes to their employment status. This research explores the legal protection of workers post-acquisition, focusing on Law No. 13 of 2003 on Manpower and analyzing relevant court decisions. The findings reveal that although acquisitions do not automatically terminate employment contracts, they frequently disrupt workers’ rights, exposing them to unexpected vulnerabilities. This study underscores the urgent need for stronger legal safeguards to protect workers from the fallout of corporate restructuring. By highlighting gaps in current labor protections, this research contributes to ongoing discussions on labor law reform, offering insights for policymakers, legal practitioners, and business leaders striving to balance corporate interests with workers’ rights in an increasingly volatile economic landscape. Ultimately, it raises a critical question: in the wake of corporate acquisitions, who truly stands up for the workers?